Morphological and molecular identification of Ellipsoidisporodochium gen. nov. (Tubakiaceae, Diaporthales) in Hainan Province, China - Liu, Shu-Bin; Zhang, Zhao-Xue; Liu, Rong-Yu; Mu, Tai-Chang; Zhang, Xiu-Guo; Li, Zhuang; Xia, Ji-Wen (Phytotaxa, 2022)
During a survey of microfungi on symptomatic leaves from Photinia serratifolia (Desfontaines) Kalkman, an interesting species of asexual ascomycetes were found. Based on multilocus phylogenies from a combined dataset of genes encoding internal transcribed spacer (ITS), large subunit of ribosomal RNA (LSU), translation elongation factor 1 alpha (tef1), part of the beta-tubulin gene region (tub2), and partial RNA polymerase II second largest subunit (rpb2), in conjunction with morphological characteristics, we describe a new genus of Tubakiaceae, Ellipsoidisporodochium gen. nov. (type species: Ellipsoidisporodochium photiniae sp. nov.). The genus has fusoid to ampulliform sporodochia and obovoid to ellipsoid conidia. Their relatedness to allied taxa are also annotated and discussed.